Targeting the Hippo Signaling Pathway for Tissue Regeneration and Cancer Therapy - Juan, Wen Chun (Genes (Basel), 2016)
The Hippo signaling pathway is a highly-conserved developmental pathway that plays an essential role in organ size control, tumor suppression, tissue regeneration and stem cell self-renewal. The YES-associated protein (YAP) and the transcriptional co-activator with PDZ-binding motif (TAZ) are two important transcriptional co-activators that are negatively regulated by the Hippo signaling pathway. By binding to transcription factors, especially the TEA domain transcription factors (TEADs), YAP and TAZ induce the expression of growth-promoting genes, which can promote organ regeneration after injury. Therefore, controlled activation of YAP and TAZ can be useful for regenerative medicine. However, aberrant activation of YAP and TAZ due to deregulation of the Hippo pathway or overexpression of YAP/TAZ and TEADs can promote cancer development. Hence, pharmacological inhibition of YAP and TAZ may be a useful approach to treat tumors with high YAP and/or TAZ activity. In this review, we present the mechanisms regulating the Hippo pathway, the role of the Hippo pathway in tissue repair and cancer, as well as a detailed analysis of the different strategies to target the Hippo signaling pathway and the genes regulated by YAP and TAZ for regenerative medicine and cancer therapy.